In vitro anti-inflammatory and anti-coagulant effects of antibiotics towards Platelet Activating Factor and thrombin - Demopoulos Constantinos A; Tsekes George; Lioni Athina; Tsogas Nickolaos; Chini Maria; Tsoupras Alexandros B; Lazanas Marios C (Journal of Inflammation, 2011)
Abstract Background Sepsis is characterized as a systemic inflammatory response that results from the inability of the immune system to limit bacterial spread during an ongoing infection. In this condition the significant mediator of inflammation Platelet Activating Factor (PAF) and the coagulant factor thrombin are implicated. In animal models, treatment with PAF-antagonists or co-administration of antibiotics with recombinant-PAF-Acetylhydrolase (rPAF-AH) have exhibited promising results. In order to examine the putative anti-inflammatory and/or antithrombotic interactions between antibiotic treatment used in sepsis with PAF and/or thrombin, we studied the in vitro effects of these compounds towards PAF or/and thrombin related activities and towards PAF basic metabolic enzymes. Methods We assessed the inhibitory effect of these drugs against PAF or thrombin induced aggregation on washed rabbit platelets (WRPs) or rabbit Platelet Reach Plasma (rPRP) by evaluating their IC50 values. We also studied their effect on Cholinephosphotransferase of PAF (PAF-CPT)/Lyso-PAF-Acetyltransferase (Lyso-PAF-AT) of rabbit leukocytes (RLs), as well as on rabbit plasma-PAF-AH, the key enzymes of both de novo/remodelling PAF biosynthesis and PAF degradation, respectively. Results Several antibiotics inhibited PAF-induced platelet aggregation of both WRPs and rPRP in a concentration-depended manner, with clarithromycin, azithromycin and amikacin exhibiting the higher inhibitory effect, while when combined they synergistically inhibited PAF. Higher concentrations of all antibiotics tested were needed in order to inhibit PAF induced aggregation of rPRP, but also to inhibit thrombin induced aggregation of WRPs. Concentrations of these drugs similar to their IC50 values against PAF activity in WRPs, inhibited also in vitro PAF-CPT and Lyso-PAF-AT activities of rabbit leukocytes, while only clarithromycin and azithromycin increased rabbit plasma-PAF-AH activity. Conclusions These newly found properties of antibiotics used in sepsis suggest that apart from their general actions, these drugs may present additional beneficial anti-inflammatory and anti-coagulant effects against the onset and establishment of sepsis by inhibiting the PAF/PAF-receptor and/or the thrombin/protease-activated-receptor-1 systems, and/or by reducing PAF-levels through both PAF-biosynthesis inhibition and PAF-catabolism induction. These promising in vitro results need to be further studied and confirmed by in vivo tests, in order to optimize the efficacy of antibiotic treatment in sepsis.